PM2.5 induces cardiac malformations via PI3K/akt2/mTORC1 signaling pathway in zebrafish larvae. (15th April 2023) - Jiang, Yan; Zhao, Xiahao; Chen, Jin; Aniagu, Stanley; Chen, Tao
Abstract: Growing evidence indicates that maternal fine particulate matter (PM2.5) exposure is linked with congenital heart diseases in the offspring. To explore the underlying molecular mechanisms, we tested the effects of a number of pharmaceutical inhibitors, and found that suppressing the PI3K/akt signaling pathway had a protective effect against cardiac defects in zebrafish larvae exposed to extractable organic matter (EOM) from PM2.5. Using genetic knockdown and a specific akt2 pharmacological inhibitor, CCT128930, we demonstrated that akt2 activation is essential to EOM-induced heart malformations. Next, we found that the EOM-induced akt2 overactivation enhances intracellular reactive oxygen species (ROS)/mitochondrial ROS production, decreases mitochondrial membrane potential levels, and elicits intrinsic apoptosis in the heart of zebrafish embryos. In addition, EOM-induced akt2 activation decreased active β-catenin levels and inhibited the expression of Wnt target genes axin2 and nkx2.5. We further demonstrated that mTORC1 phosphorylation mediates the adverse effects of akt2 on intrinsic apoptosis and canonical Wnt signaling in the heart of zebrafish larvae exposed to EOM. Moreover, EOM-induced akt2 activation is mediated via aryl hydrocarbon receptor (AHR)/ROS-induced PTEN inhibition. In conclusion, our results indicate that PM2.5 activates PI3K/akt2/mTORC1 signaling via AHR/ROS-induced PTEN suppression, which leads to mitochondrial-mediated intrinsic apoptosis and Wnt signaling suppression, resulting in cardiac defects in zebrafish larvae. Graphical abstract: Image 1 Highlights: PI3K/akt2 mediates PM2.5-induced cardiac malformations in zebrafish larvae. PM2.5-induced akt2 overactivation elicites intrinsic apoptosis. PM2.5-induced akt2 overactivation inhibits Wnt signaling. mTORC1 mediates the adverse effects of akt2 on apoptosis and Wnt signaling. PM2.5 activates akt2 via AHR/ROS mediated PTEN inhibition.